PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT SAT NUSAPERSADA TBK - Lase, Marnita; Suhardi (LPPM Universitas Putera Batam, 2021)
In achieving organizational goals, the company seeks to advance employee performance to the fullest. Companies need to pay attention to the mental condition of their employees not only with adequate wages and facilities. Often employees experience work stress and work conflicts that can affect the employee's performance. Humans resources are an important asset in the company because they are the driving force for the company's progress. For this reason, companies must pay attention to their human resources to maintain their quality. However, the company experienced problems because the decline in employee performance was not as good as when they first worked at the company. Work conflict and work stress are common in companies and are often difficult to overcome. Based on this, the company tries to find the causal factors and how to handle conflicts that occur between employees, both individually and in groups. These studies aims determining the effects of work conflict and work stress on employee performance at PT Sat Nusapersada Tbk. That researches designed using researches designed and quantitative causality research methods. Data collection techniques by distributing questionnaires to 108 employees of PT Sat Nusapersada Tbk, especially in the Xiaomi Department. The results of this study indicate that work conflict (X1), work stress (X2) partially and simultaneously significant effect on employee performance (Y). Keywords: Employee performance; Work conflict; Work stress.